CONTRASTIVE STUDY OF DIPLOMATIC TERMS IN POLITICAL TEXTS - Almuratov Asqar Ravshan ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The article analyzes the structure of diplomatic terms in the Uzbek language. The article highlights the topics of classification of diplomatic terms depending on their structure, and also describes the features of the semantics of some terms. The materials of this article can be used by linguists, people involved in the field of diplomacy and researchers.